Posibilitas Eksistensi Jenis Tindak Pidana Pencucian Uang Stand Alone Money Laundering Di Indonesia - Muh. Afdal Yanuar (Faculty of Law, Andalas University, 2021)
Refer to the Constitutional Court Decision’s Number 77/PUU-XII/2014, it can be understood that money laundering offences is a follow up crimes. So that, every prosecution and proving to money laundering offences are carried out, the property which suspected as an object of money laundering offences must link to crime, even in terms of the predicate offences is not proven first, because of the money launderer is not a materiele dader of predicate offences, as an Article 69 Money Laundering Laws contextualization’s. In the context of money laundering proving as an Article 69 Money Laundering Laws, the linkages between money laundering offences and proceeds of crime and predicate offences, must be described. Because of in stand alone money laundering proving and prosecuting money laundering offences without also necessarily proving and prosecuting the predicate offences was probably, for example, if predicate offences of money laundering was unsufficient evidence or unable to proven, so that the existence of stand alone money laundering in Indonesia in status quo refer to Constitutional Court Decision’s Number 77/PUU-XII/2014 is not possible. However, the existence of stand alone money laundering can be possible here in Indonesia, if in the future (ius constituendum): (a) there is provision in money laundering’s criminal procedure laws which regulated in the laws, that at least recognize of stand alone money laundering’s existence; or (b) The Criminal Proving System which recognized in Indonesia in originally set forth negative wettelijk system, transformed into the conviction intime system or laconviction raisonee system